2018
DOI: 10.1007/s00405-018-4993-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of “trigeminal training” on trigeminal sensitivity and self-rated nasal patency

Abstract: PurposePatients with the feeling of a congested nose not always suffer from an anatomical obstruction but might just have a low trigeminal sensibility, which prevents them from perceiving the nasal airstream. We examined whether intermittent trigeminal stimulation increases sensitivity of the nasal trigeminal nerve and whether this effect is accompanied by subjective improvement of nasal breathing.MethodThirty-five patients (Mage = 58.4 years; SD = 14.8; Minage = 21 years; Maxage = 79 years; 43% females) and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Especially Eccles et al analysed the positive effect of menthol stimulating trigeminal perception and improving subjective sensation of nasal airflow without altering inner nasal space (7,21) . "Trigeminal training" may even improve CO2 sensitivity and the feeling of nasal patency, while not having a relevant impact on lateralisation scores (22) . In contrast, altering inner nasal space, as mentioned above, does not always improve subjective sensation of nasal airflow (6,18) .…”
Section: Discussionmentioning
confidence: 99%
“…Especially Eccles et al analysed the positive effect of menthol stimulating trigeminal perception and improving subjective sensation of nasal airflow without altering inner nasal space (7,21) . "Trigeminal training" may even improve CO2 sensitivity and the feeling of nasal patency, while not having a relevant impact on lateralisation scores (22) . In contrast, altering inner nasal space, as mentioned above, does not always improve subjective sensation of nasal airflow (6,18) .…”
Section: Discussionmentioning
confidence: 99%
“…The patients were asked to rate their subjective ability to smell and taste on an analogue scale of 1-10 (1 = bad, 10 = good). In addition, the subjective patency of the nose was asked about via a 5-point scale, as nasal patency is a barometer of trigeminal sensitivity [5].…”
Section: Methodsmentioning
confidence: 99%
“…For example, the long duration of training increases the chances of losing participants with the attrition rate as high as 45% in some 6-month studies (Lamira et al, 2019), although this was not the case in the present study. Compliance is important as one recent study of trigeminal training showed that the correlation between training time and improvement of trigeminal sensitivity became insignificant after controlled for the compliance (Oleszkiewicz et al, 2018). Although the actual compliance was assumed to be highly based on the personal interviews with the patients following OT, the inclusion of training diaries or a modified training device (Saatci et al, 2020) should be considered in future research.…”
Section: Discussionmentioning
confidence: 99%